Defect evolution in laser powder bed fusion additive manufactured components during thermo-mechanical testing - Xu, Zhengkai; Hyde, Christopher J.; Thompson, Adam; Leach, Richard K.; Maskery, Ian; Tuck, Christopher; Clare, Adam T. (2017)
The mechanical performance of additively manufactured (AM) components remains an issue, limiting the implementation of AM technologies. In this work, a new method is presented, to examine the evolution of defects in an Inconel 718 two-bar test specimen, manufactured by laser powder bed fusion AM, during thermo-mechanical testing. The test was interrupted at specific extensions of the specimen, and X-ray computed tomography measurements performed. This methodology has allowed, for the first time, the evolution of the defects in an AM specimen to be studied during a thermo-mechanical test. The number and size of the defects were found to increase with time as a result of the thermo-mechanical test conditions, and the location and evolution of these defects have been tracked. Defect tracking potentially allows for accurate prediction of failure positions, at the earliest possible stage of a thermo-mechanical test. Ultimately, when the ability to locate defects in this manner is coupled with manipulation of build parameters, laser powder bed fusion practitioners will be able to further optimise the manufacturing procedure in order to produce components of a higher structural integrity.